2006
DOI: 10.1038/sj.ki.5000005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of renal kallikrein by a high potassium diet in rats with intense proteinuria

Abstract: Injury of the renal tubulointerstitial compartment is recognized to play an important role in hypertension. Its damage may in turn, impair the activity of vasodepressor systems, like the kallikrein-kinin, in blood pressure regulation. The overload proteinuria model induces tubulointerstitial injury with activation of the renin-angiotensin system, but renal kallikrein and the development of hypertension have not received special attention. Sprague-Dawley rats received seven intraperitoneal doses of bovine serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…We found that AO induced mild arterial hypertension. Hypertension is not a finding in female Lewis rats with AO (1) but it has been reported by other groups in SpragueDawley rats (2).…”
Section: Discussionmentioning
confidence: 63%
“…We found that AO induced mild arterial hypertension. Hypertension is not a finding in female Lewis rats with AO (1) but it has been reported by other groups in SpragueDawley rats (2).…”
Section: Discussionmentioning
confidence: 63%
“…Control experiments have shown that these inhibitors have no effect on the enzymatic activity of purified rat salivary and urinary kallikreins. Moreover, enzymatic activity obtained under these conditions was completely abolished by antiurinary kallikrein antiserum but not by nonimmune serum, indicating that the activity indeed corresponds to kallikrein activity (3,5,50). Values, expressed as milliunits per milliliters, were calculated relative to milligrams of urinary creatinine to allow for differences in volume.…”
Section: Urinary Kallikrein Activity Assaymentioning
confidence: 99%
“…The first period (induction of tubulointerstitial damage) comprised an overload proteinuria with a normosodic diet for 2 wk followed by a washout recovery period lasting another 2 wk (also with a normal sodium diet). Overload proteinuria without previous nephrectomy (to avoid the effects of renal mass reduction) was performed using one intraperitoneal injection per day for 14 days of 2 g BSA (Fraction V, A-4503; Sigma) administered as 6 ml of a 33.3% BSA solution dissolved in 0.9% sterile saline, as previously described (2,5,9,15,16).…”
Section: Experimental Design and Groupsmentioning
confidence: 99%
See 2 more Smart Citations